Butt or face? : can you tell which end you're looking at? - Lavelle, Kari (Lavelle, Kari. Butt or face?, 2023)
"Butt or Face offers kids a delightfully cheeky challenge: examine a close-up photo of an animal, and then guess whether you're looking at the top or the...um...bottom. The answer is revealed on the next page with a complete photo of the animal! Also included are factual animal details along with how these animals use camouflage or other trickery to engage with their home. Readers will discover animals like the Cuyaba dwarf frog whose backside looks like a pair of eyes, the Mary River turtle that breathes through its butt, and many more!" --